2011
DOI: 10.4070/kcj.2011.41.5.235
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Ambulatory Arterial Stiffness Index and Blood Pressure Variability in Hypertensive Patients

Abstract: Background and ObjectivesAmbulatory arterial stiffness index (AASI) is well known as a predictor of cardiovascular mortality in hypertensive patients. Mathematically, AASI reflect the standard deviation (SD) of blood pressure (BP) variation. AASI is measured higher levels in non-dipper than dipper. Thus, AASI has a possibility of not only reflecting arterial stiffness but also BP variability and/or autonomic nervous dysfunction.Subjects and MethodsConsecutive data from 418 untreated hypertensive patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…In addition, nondipper status was found to be a predictor of high AASI in the entire population as well as the RA group. Similar to this result, Lee et al [28] showed nondipper status to be an independent predictor of high AASI and the authors concluded that AASI is affected by autonomic dysregulation. However, although the proportion of nondipper individuals was similar in the two groups (63.6% in the RA group vs. 60.6% in the control group, P = 0.800), a significant association between AASI and nondippers was not found in the control group.…”
Section: Ra Female Malesupporting
confidence: 65%
“…In addition, nondipper status was found to be a predictor of high AASI in the entire population as well as the RA group. Similar to this result, Lee et al [28] showed nondipper status to be an independent predictor of high AASI and the authors concluded that AASI is affected by autonomic dysregulation. However, although the proportion of nondipper individuals was similar in the two groups (63.6% in the RA group vs. 60.6% in the control group, P = 0.800), a significant association between AASI and nondippers was not found in the control group.…”
Section: Ra Female Malesupporting
confidence: 65%
“…Previous studies have shown AASI be affected by the extent of the nocturnal BP fall, 3-7 BP variability expressed as the standard deviation, [12][13][14][15] and baroreflex sensitivity, 16 and therefore antihypertensive treatment which could modify these factors might in turn affect AASI in a manner independent of changes in arterial stiffness. Furthermore, previous findings, [17][18][19] taken together with the present findings, have suggested that AASI represents an integrated measure of ventriculo-arterial coupling, depending on both arterial (arterial stiffness and systemic vascular resistance) and cardiac factors (stroke volume and heart rate).…”
Section: Discussionmentioning
confidence: 98%
“…For example, in one study, pulse pressure variability, systolic BP variability, diastolic BP variability and nondipper status were determined to be independent predictors of AASI, suggesting that AASI is a parameter that reflects BP variability as well as arterial stiffness. 17 Furthermore, systolic BP variation and diastolic BP variation have been shown to correlate with intima-media thickness, pulse wave velocity and AASI, with 24-h diastolic BP variation having a significant association with AASI in a multiple regression analysis. 37 Similarly, AASI has been found to negatively correlate with the morning surge in diastolic BP, daytime diastolic BP, 24-h mean arterial pressure variability, and nocturnal dips in systolic BP, diastolic BP and mean arterial pressure.…”
Section: Discussionmentioning
confidence: 98%
“…From a mathematical standpoint, the possibility exists that assessment of AASI may be confounded by other parameters derived from ambulatory BP monitoring, including BP variation, pulse pressure, nocturnal dipping, and the morning BP surge. 17,18 These measures of variability in BP have been documented by some reports to be prognostic markers of target-organ damage and cardiovascular disease. [19][20][21][22][23][24] In addition to AASI, several other factors have been reported to correlate with stiffer vessels in patients with hypertension, including a nondipper pattern, and other markers such as pulse pressure.…”
Section: Introductionmentioning
confidence: 99%